1989
DOI: 10.7589/0090-3558-25.2.297
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Methods to Establish the Prevalence of Lead Shot Ingestion in Mallards (Anas platyrhynchos) from The Netherlands

Abstract: Two collection methods for screening the mallard (Anas platyrhynchos) population in the Netherlands for the ingestion of spent lead shot were compared. One method consisted of examination of gizzards from mallards shot by hunters (n = 2,859) and the other method consisted of examination of gizzards from mallards caught in duck traps (n = 865). The 95% confidence interval of lead shot ingestion in the mallard population estimated by the first method was 1.7 to 2.9% and by the second method 1.1 to 3.1%. These va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There are several potential sources of error in the data presented that may affect estimates of exposure of upland birds to spent lead shot. Studies on waterfowl in the United States have shown that the proportion of hunter-killed birds with lead shot in their gizzards is 1.6 to 3.8 times higher than the proportion in researcher-collected birds [5,51], although Lumeij and Scholten [52] reported no collection bias for mallard ducks (Anas platyrhynchos) in the Netherlands. This suggests that lead-intoxicated birds are more susceptible to being shot during a hunt.…”
Section: Biases In Assessing the Exposure Of Upland Birds To Spent Lementioning
confidence: 98%
“…There are several potential sources of error in the data presented that may affect estimates of exposure of upland birds to spent lead shot. Studies on waterfowl in the United States have shown that the proportion of hunter-killed birds with lead shot in their gizzards is 1.6 to 3.8 times higher than the proportion in researcher-collected birds [5,51], although Lumeij and Scholten [52] reported no collection bias for mallard ducks (Anas platyrhynchos) in the Netherlands. This suggests that lead-intoxicated birds are more susceptible to being shot during a hunt.…”
Section: Biases In Assessing the Exposure Of Upland Birds To Spent Lementioning
confidence: 98%
“…There are several potential sources of error in the data presented that may affect estimates of exposure of upland birds to spent lead shot. Studies on waterfowl in the United States have shown that the proportion of hunter-killed birds with lead shot in their gizzards is 1.6 to 3.8 times higher than the proportion in researcher-collected birds [5,51], although Lumeij and Scholten [52] reported no collection bias for mallard ducks (Anas platyrhynchos) in the Netherlands. This suggests that lead-intoxicated birds are more susceptible to being shot during a hunt.…”
Section: Biases In Assessing the Exposure Of Upland Birds To Spent Lementioning
confidence: 99%
“…Prevalence of ingestion of lead pellets in mallard (Anas platyrhynchos), a widespread species, is 1.7-2.9% in The Netherlands (Lumeij and Scholten 1989), 4.2% in Great Britain (Mudge 1983), and 8.1% in USA (Sanderson and Bellrose 1986), although in some areas, such as Texas, prevalence reached 36.4% before the ban of lead shot (Moulton et al 1988).…”
mentioning
confidence: 97%